Measuring screen time among adolescents: test–retest reliability of HBSC questionnaire items across two countries - Matusova, Michaela; Maracek, Marek; Pavelka, Jan; Ng, Kwok; Medina, Catalina; Tylsarova, Nikola; Bucksch, Jens; Hamrik, Zdenek (BioMed Central, 2026)
Background
Increasing recreational screen time among adolescents is linked to adverse health outcomes like obesity and poor mental health. This highlights the need for reliable tools to monitor screen-based behaviours. The present study examined the test–retest reliability of recreational screen-time items from the Health Behaviour in School-aged Children (HBSC) questionnaire across culturally diverse adolescent populations.
Methods
Using a test–retest design with a 2–3 week interval, we collected data from 750 adolescents (48.8% boys, mean age 15.29 years, SD 2.37) in Mexico (n = 233, aged 10–15y) and Czechia (n = 517, aged 10–18y) in 2022–2024. Self-reported time spent on gaming, social networking, video watching, and internet browsing were evaluated using Intraclass Correlation Coefficients (ICCs) for continuous measures and Cohen’s kappa for dichotomized outcomes (< 2 vs. ≥ 2 h/day), with analyses stratified by age, gender, and country.
Results
Gaming and social networking demonstrated moderate-to-good reliability (ICC = 0.70–0.74, κ = 0.64–0.65, 82–83% unchanged responses). Video watching and browsing were less stable (ICC = 0.52–0.63, κ = 0.41–0.47). Czech primary school students exhibited the highest consistency (ICC = 0.76–0.81), while Mexican students completed the items with lower reliability (ICC = 0.43–0.54). Older adolescents (16–18 years) and girls reported greater stability for gaming and social networking, respectively.
Conclusions
The screen-time items tested in this study showed acceptable test–retest reliability across countries, age groups, and sexes, particularly for gaming and social networking. These findings support their use in global adolescent health surveillance, while highlighting the need for refinement of less stable domains such as video watching and internet browsing. Given that samples were not nationally representative, findings should be interpreted within these specific contexts. Future research should enhance measurement precision and inform public health efforts to monitor and address screen-time related health risks.